The Influence of Cultural Factors on Accounting Practices and Disclosure Choices (gjstudies, 2020)
This research investigates the profound and often overlooked influence of cultural dimensions on accounting practices and disclosure choices, moving beyond traditional economicand institutional explanations. While prior literature has acknowledged cultural effects,this study introduces a novel methodological framework that integrates computationalcultural analytics with accounting data to reveal previously undetected patterns. Wedevelop a unique cultural proximity index derived from linguistic analysis of corporatecommunications, national cultural value surveys, and historical institutional data, whichwe correlate with specific accounting conservatism measures, disclosure transparencyscores, and earnings management behaviors across 42 countries. Our findings demonstrate that cultural factors explain approximately 31% of the variance in accountingpractice adoption beyond what is accounted for by legal systems and economic development alone. Specifically, we identify that high uncertainty avoidance cultures exhibitsignificantly greater accounting conservatism and lower discretionary accruals, while individualistic societies demonstrate more extensive voluntary disclosures but also higherearnings smoothing. The research introduces the concept of ’cultural accounting pathdependence,’ showing how historical cultural imprints persist despite globalization pressures. We also reveal a previously undocumented phenomenon: cultures with high longterm orientation are adopting hybrid accounting practices that blend international stan1Published: 2020-09-20dards with traditional valuation methods, creating unique local adaptations. This studycontributes to accounting theory by providing a more nuanced, culturally-grounded explanation for international accounting diversity and offers practical implications for globalstandard-setters, multinational corporations, and cross-border investors seeking to navigate accounting differences not merely as technical variations but as expressions of deepercultural logic.